Solo leveling. 12 - Ch'ugong; Ch'ugong; h-goon (Anime creator) (Ize Press, 2025)
"Jinwoo faces off against the Monarchs for the first time, and while he's undeniably the strongest hunter in the world, three otherworldly beings prove to be too much for him! But as Jinwoo is about to find out, death means little to the Shadow Monarch, King of the Dead. As Jinwoo Sung finally confronts the true source of his newfound powers, in the real world, a person thought to be lost forever steps in to defend his son's defenseless body!"--yenpress.com.